IMPLEMENTASI SANITASI TOTAL BERBASIS MASYARAKAT (STBM) BERSAMA PROGRAM KKN DI DESA TARO GIANYAR - N.M.U, Dwipayanti; N. K., Sutiari (Buletin Udayana Mengabdi, 2013)
One target of MDG 2015 is to reduce by half the pulation without access to water and basic sanitation. The Health Ministry of Indonesia has an effort to increase basic sanitation access through National Strategy of Community Based Total Sanitation (STBM) started from 2008. According to data from the local primary health care (Puskesmas) Tegalalang II, the sanitation coverage in some area of Taro Village are low. For that reason, in cooperation with Health Agency of Gianyar, Puskesmas Tegalalang II, the activity of KKN in Taro Village was integrated with STBM program focusing on hygiene behavior change in terms of stop open defecation without any subsidy provided. The preparation was started with training of STBM facilitator participated by KKN students. It was then followed by triggering of stop open defecation as well as promoting hand washing with soap in Banjar Tebuana, Taro, Gianyar. The trigering and promoting activities were conducted through participatory rural appraisal (PRA) method that utilising Participatory Hygiene and Sanitation Transformation (PHAST). In order to have baseline data in sanitation, then verification of sanitation facilities already built in the village was carried out. From the trigering process only 3 families that commited to build toilet. The community always consider that poverty as the main reason why they could not afford for a toilet. From the verification result, only 21,21% families that have toilet, and only 38% of those toilet that categorised as hygiene toilet. Moreover, only 55,55% of families that have facilities for washing hand with soap.Based on the trigering and verification result, it is recommended that facilitating this village to rapidly reduce the number of families without access to basic sanitation is very important to continue. The role of sanitarian at Puskesmas cooperated with village government to facilitate their community in pursing behavior change is also very crucial.